Peran Suami Dalam Perawatan Kehamilan Hingga Nifas - Nurrohmah, Anjar; Indarwati (STIKES Ngesti Waluyo, 2024)
According to WHO (World Health Organization), the maternal mortality rate reached a ratio of 211 deaths per 100,000 live births globally. Data from the Central Statistics Agency of Indonesia in 2015 showed that maternal mortality on the island of Java-Bali ranked in second place at 247 deaths per 100,000 live births. The government has made various efforts to reduce maternal and child mortality. In order to carry out optimal pregnancy care, mothers need support from people around them. The research aims to describe the husband's role in care from pregnancy to postpartum during the new normal era of COVID-19. Method: Cross-sectional research with recall survey approach was conducted from March to June 2022 in the Sidodadi sub-district. The study population was the husbands of the mothers who had given birth. The population was 110, and a sample of 53 people was obtained using purposive sampling technique. The inclusion criteria were husbands of mothers with children aged ≤ 1 year, and willing to be respondents. This research instrument is a Google Form questionnaire. The data were analyzed using univariate analysis. The results of this study showed that most respondents indicated that the role of the husband during pregnancy to postpartum was good, with 98%.